Correlation between wear and fatigue properties and the lifetime of silver coated electrical connectors - Song, Jian; Tuelling, Soeren; Hengstler, Jonas (Wear : an international journal on the science and technology of friction, lubrication and wear)
In a previous paper, the correlation between the wear resistance of coatings and the lifetime of electrical connectors under fretting load was discovered. Based on this knowledge, various modifications of silver-based coatings with markedly increased wear resistance have been developed, and a calculation model for predicting connector lifetime has been formulated. Investigations on silver-coated electrical contacts with increased wear resistance show extended lifetimes in fretting wear and fretting corrosion tests, and the calculation model with various modified coating materials can be validated. However, contacts with very high wear-resistant coatings fail earlier than the specific wear coefficient and the calculation model prediction suggest. The in-depth investigation of the coating material and the wear scar revealed the reasons for this unexpectedly shorter lifetime. The high wear resistance of modified silver coatings is achieved by increased micro-hardness. Both coatings with coating materials of high hardness and high thickness can lead to longer lifetimes under fretting load. However, increased fretting cycles can also cause fatigue and electrical contacts can fail due to delamination of the surface coating caused by fretting fatigue, and this delamination can lead to a sudden exposure of the base material, thus enabling its corrosion. Therefore, both wear resistance and fatigue resistance should be increased in order to achieve a long lifetime of electrical contacts under fretting load.
Keywords: Fretting; Wear; Fatigue; Lifetime; Electrical contacts